2020
DOI: 10.3390/microorganisms8091409
|View full text |Cite
|
Sign up to set email alerts
|

Cutibacterium acnes Biofilm Study during Bone Cells Interaction

Abstract: Cutibacterium acnes is an opportunistic pathogen involved in Bone and Prosthesis Infections (BPIs). In this study, we observed the behavior of commensal and BPI C. acnes strains in the bone environment through bacterial internalization by osteoblast-like cells and biofilm formation. For the commensal strains, less than 1% of the bacteria were internalized; among them, about 32.7 ± 3.9% persisted intracellularly for up to 48 h. C. acnes infection seems to have no cytotoxic effect on bone cells as detected by LD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…However, some strains, such as BPI 2 or BPI4, showed a very fine biofilm, with only a few aggregates. In our previous publication [ 38 ], we have observed that BPI biofilms were more important than commensal ones before internalization. In this case, our results were concordant.…”
Section: Resultsmentioning
confidence: 96%
See 4 more Smart Citations
“…However, some strains, such as BPI 2 or BPI4, showed a very fine biofilm, with only a few aggregates. In our previous publication [ 38 ], we have observed that BPI biofilms were more important than commensal ones before internalization. In this case, our results were concordant.…”
Section: Resultsmentioning
confidence: 96%
“…This could be explained by the presence of large aggregates which could lead to bacteria death [ 39 ]. From a global point of view, the percentage of living bacteria within biofilm was higher in the dynamic than in the static model with the exception of C18 strains; with an average of 88.5% (±1%) for C2, C5, and C8 vs. an average of 56.8% (±9%) in the static model (data from reference [ 38 ]).…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations